Fluorescence properties of selected benzo[c]phenantridine alkaloids and studies of their interaction with CT DNA - Urbanová, Jana; Lubal, Premysl; Slaninová, Iva; Táborská, Eva; Táborský, Petr (Analytical and bioanalytical chemistry, 2009)
The spectral, especially fluorescence properties, of seven selected quaternary benzo[c]phenantridine alkaloids (sanguinarine, chelerythrine, chelirubine, sanguirubine, chelilutine, sanguilutine, and macarpine) were studied in presence and in absence of double-stranded DNA. This study has proved dramatic differences in fluorescence emission of all studied alkaloids in presence of calf thymus DNA in comparison to fluorescence of free alkaloids. The most remarkable are changes in emission spectra of macarpine, chelirubine, and sanguirubine. Association constants (logK) for interaction of all studied alkaloids with CT DNA were calculated.
Keywords: Benzophenanthridines; Reproducibility of Results; Fluorescence; DNA; Spectrophotometry, Ultraviolet; Quantum Theory; Spectrometry, Fluorescence; kvantová teorie; benzofenantridiny; spektrofotometrie ultrafialová; fluorescenční spektrometrie; fluorescence; reprodukovatelnost výsledků